Historiography of Scythian migration in the mirror of information technologies - Kokorina, Yulia Georgievna; Vagabov, Machach Mustafaevich; Lelina, Helena Ivanovna (Linguistics and Culture Review, 2021)
This article is devoted to the insight of the migration process in the diachronic aspect on the example of Scythians history. This choice is caused by the fact that the information about the Scythians, their arrival in Eastern Europe and movements in the ancient Oecumene, is one of the main problems of Scythian archaeology. A significant range of sources contains information about the arrival of the Scythians and their movements in Europe. These sources include both the works of historians of Antiquity and Modern Times, as well as the works of modern archaeologists. The change of ideas about the Scythians migration is reviewed in accordance with the concept of the information technology shifts, which was put forward by Russian scientists Y.L. Shchapova and S.N. Grinchenko, specifically: information technology of articulate speech and language, information technology of writing, information technology of book printing, information technology of computers, information technology of networks. As result, conclusions were drawn from oral traditions about the vision changes on the causes of migration, about the arrival of a mythological hero – first ancestor at an unpopulated land, wars and tribal confrontation in the era of information technology of speech and language and information technology of writing.